Indigenisation of Global Norms: Norm Localization Analysis on LGBTQ+ Acceptance in Surabaya, Indonesia - Chairun Nisya; Dwi Ardhanariswari Sundrijo (Salasika, 2022)
In the era of globalisation, norms can easily travel and transfer worldwide; they can also be adapted into certain local norms. Indonesian public acceptance of global norms is heavily affected by religious norms, which are deeply conservative. The acceptance of the LGBTQ+ community by the Indonesian public has been its hard case for that reason. However, in Surabaya, one of the biggest cities in Indonesia, religious norms have been utilised by GayA Nusantara (GN), a local NGO advocating for the acceptance of the LGBTQ+, as an effective tool to reconstruct public perception towards the LGBTQ+ community. This research explains how the GN approach helped the Surabayan accept the LGBTQ+ community. This research highlights the importance of the history of local culture and local wisdom that proves that Indonesian society – to certain degrees – has long been relatively accepting of gender diversity as part of their day-to-day life. However, when it comes to accepting LGBTQ+ as part of global norms, Indonesian still seems reluctant to be open to it. Within this unique context, this research aims to explain the localisation process of the global norms on LGBTQ+ as part of the advocacy strategy conducted by GN. Applying the interpretative research method allows the researcher to interpret the result based on the data without letting the theory and/or indicators shape the research outcome.